Cardiovascular responses to high-intensity exercise: A systematic literature review comparing trained and untrained individuals - Satrianingsih, Baiq; Risma; Dupri; Yulianto, Ari Gana (Journal Sport Area, 2025)
Background: High-intensity exercise induces distinct cardiovascular responses, but systematic comparisons between trained and untrained individuals remain limited. Objective: The primary objective of this study was to compare cardiovascular responses to HIIT specifically heart rate, blood pressure, and blood lactate levels and to identify factors influencing these differences. Methods: A systematic literature review following the PRISMA framework was conducted for this study. The initial search on the Scopus database using keywords such as “High-Intensity Exercise,” “Cardiac Output,” “Trained,” and “Untrained” yielded 380 articles. After a rigorous screening process, which applied strict inclusion and exclusion criteria including the requirement that articles be published in Q1-Q4 ranked journals between 2014 and 2024 a final set of 10 primary articles was selected for in-depth analysis. Findings/Results: High Intensity Interval Training effectively improves cardiovascular function in both trained and untrained individuals. Significant increases in cardiac output and VO₂ max are observed, particularly in trained cyclists. While untrained individuals also benefit, superior cardiovascular adaptations are seen in those who are trained. Furthermore, HIIT is proven to be safe; it does not increase the risk of cardiovascular dysfunction and even has a cardioprotective effect, demonstrated by an increase in cardiac ejection fraction. Conclusion: This review provides the first systematic synthesis comparing cardiovascular responses to high-intensity exercise between trained and untrained individuals. The findings highlight the importance of training status in exercise prescription and offer practical insights for coaches and health practitioners in optimizing high-intensity training programs.